Tingkat Literasi Keuangan Mahasiswa dan Faktor-Faktor Yang Mempengaruhinya pada Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar - Hariyanti Hariyanti; Megawhati Artiyany (Al-Buhuts, 2020)
This study aims to analyze the level of financial literacy and the factors that influence it at the Tri Dharma Nusantara Makassar College of Economics and to analyze how the influence of gender, age, year class, study program and residence affects the level of student financial literacy. The number of samples in this study were 458 (four hundred and fifty eight) respondents. The data analysis method is descriptive statistics and multiple dummy regression. The data collection technique was carried out by distributing questionnaires to students who were research respondents. The sample selection in this study was carried out with the accidental sampling method. The overall level of student financial literacy is> 84% - 100% which is included in the very high category and> 68% -84% which is included in the high category. The test results found that gender has a positive and significant effect on the level of financial literacy. This shows that men are better able to manage their finances than women. Meanwhile, age, year of class, study program and place of residence have no effect on the level of student financial literacy. Higher education institutions are expected to be able to evaluate course material related to the level of student financial literacy. Standardization of material is an important agenda in order to provide equal understanding of students